Disparities in health condition diagnoses among aging transgender and cisgender medicare beneficiaries, 2008-2017 - Hughto, Jaclyn M. W.; Varma, Hiren; Babbs, Gray; Yee, Kim; Alpert, Ash; Hughes, Landon; Ellison, Jacqueline; Downing, Jae; Shireman, Theresa I. (Frontiers in Endocrinology, 2023)
Background: The objective of this research is to provide national estimates of the prevalence of chronic health conditions of aging trans feminine, trans masculine, and non-binary Medicare beneficiaries. Quantification of the health burden across sex assigned at birth and gender can inform prevention, research, and allocation of funding for modifiable risk factors. Methods: Using 2009–2017 Medicare fee-for-service data, we implemented an algorithm that leverages diagnosis, procedure, and pharmacy claims to identify age-entitled transgender Medicare beneficiaries and stratify the same by inferred gender: trans feminine and nonbinary (TFN), trans masculine and nonbinary (TMN), and unclassified. We selected a 5% random sample of cisgender individuals for comparison. We descriptively analyzed (means and frequencies) demographic characteristics (age, race/ethnicity, US census region, months of enrollment) and used chi-square, t-tests, and ANOVAs to determine between-group (transgender vs. cisgender) and within-group-gender differences (e.g., TMN, TFN, unclassified) difference in demographics (p<0.05). We then used logistic regression to estimate and examine within and between-gender-group differences in the predicted probability of 25 health conditions, con- trolling for gender category, age, race/ethnicity, enrollment length, and census region. Results: The analytic sample included 9,975 transgender (TFN n=4,198; TMN n=2,762; unclassified n=3,015) and 2,961,636 cisgender (male n=1,294,690, female n=1,666,946) beneficiaries. The majority of the transgender and cisgender samples were under age 70 and White, non-Hispanic. The largest proportion of transgender and cisgender beneficiaries were from the South. On average, transgender individuals had more months of enrollment than cisgender individuals. In adjusted models, aging TFN or TMN Medicare beneficiaries had the highest probability of each of the 25 health diagnoses studied relative to cisgender males or females. TFN beneficiaries had the highest burden of health diagnoses relative to all other groups. Conclusion: These findings document disparities in key health condition diagnoses among transgender Medicare beneficiaries relative to cisgender individuals. Future application of these methods will enable the study of rare and anatomy-specific conditions among hard-to-reach aging transgender populations and inform interventions and policies to address documented disparities.